2000
DOI: 10.1007/s003350010138
|View full text |Cite
|
Sign up to set email alerts
|

Gasdermin (Gsdm) localizing to mouse Chromosome 11 is predominantly expressed in upper gastrointestinal tract but significantly suppressed in human gastric cancer cells

Abstract: Amplification of proto-oncogenes associated with their over-expression is one of the critical carcinogenic events identified in human cancer cells. In many cases of human gastric cancer, a proto-oncogene ERBB-2 is co-amplified with CAB1 genes physically linked to ERBB-2, and both genes are over-expressed. The amplified region containing ERBB-2 and CAB1 was named 17q12 amplicon from its chromosomal location. The syntenic region corresponding to the 17q12 amplicon is well conserved in mouse. In this study we iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
159
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 179 publications
(169 citation statements)
references
References 10 publications
3
159
0
Order By: Relevance
“…Thus, we concluded that this cDNA clone encodes human GSDM. Mouse Gsdm expression has been identified in the esophagus, stomach and skin (Saeki et al, 2000). Human GSDM mRNA, in a similar manner, was detected in the epithelium of the stomach, esophagus, mammary gland and skin (Figure 1 and data not shown).…”
Section: Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…Thus, we concluded that this cDNA clone encodes human GSDM. Mouse Gsdm expression has been identified in the esophagus, stomach and skin (Saeki et al, 2000). Human GSDM mRNA, in a similar manner, was detected in the epithelium of the stomach, esophagus, mammary gland and skin (Figure 1 and data not shown).…”
Section: Resultssupporting
confidence: 57%
“…The human cDNA clone obtained has 89% similarity in amino-acid sequence to mouse Gsdm (data not shown). A database search revealed that the human cDNA sequence is located on the human chromosome 17q21, which is syntenic to the region containing Gsdm on mouse chromosome 11 and genomic Southern blot analysis demonstrated that only one Gsdm homolog is present in the human genome (Saeki et al, 2000). Thus, we concluded that this cDNA clone encodes human GSDM.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations